På gjengrodde stier (1949): Pasienten som forteller - Nesby, Linda Hamrin (Nordlit, 2016)
In this article, I discuss Knut Hamsun’s last book On Overgrown Paths [På gjengrodde stier] (1949) from the perspective of a pathography, meaning an autobiography that focuses on a person’s illness and its consequences. Due to his actions during WWII, Hamsun was subjected to a psychiatric examination in 1947 and diagnosed as having permanently impaired mental faculties. Hamsun opposed this diagnosis, and the book both aims at demonstrating his mental ability and depicting his experience of being an unwilling patient. This article looks at how the autobiographical narrator reflects upon his experiences as a patient, and how the text contains a certain critique of the clinic and the patient-doctor relationship. It sheds light on how the motif of travel and quest is important for the narrator’s experience of being ill, and it concludes with a brief discussion of how medicine and literature are disciplines that may benefit from an interdisciplinary approach to studying both fiction and autobiographical literature.